Component-Resolved Diagnosis of American Cockroach (Periplaneta americana) Allergy in Patients From Different Geographical Areas - Wangorsch, Andrea; Jamin, Annette; Eichhorn, Stephanie; Pablos, Isabel; Sharma, Swati; Schweidler, Bettina; Kastner, Bianca; Wildner, Sabrina; Saloga, Joachim; Führer, Frank; Reyna Orozco, Reinaldo Rafael; Sherkat, Roya; et al. (Frontiers in Allergy, 2021)
Background: Manifestation of respiratory allergy to American cockroach (Periplaneta americana) is prominent in the subtropical and tropical areas. However, co-existing perennial indoor inhalant allergies frequently compromise clinical diagnosis of cockroach allergy, and analysis of sensitization pattern is limited by the lack of Periplaneta allergens widely available for component resolved diagnostics (CRD). Objective: To evaluate a collection of previously known and novel recombinant Periplaneta allergens for CRD in cockroach allergy. Methods: A panel of nine recombinant Periplaneta allergens (Per a 1-5, 7-10) was generated, purified and subjected to physicochemical characterization by applying circular dichroism spectroscopy, dynamic light scattering, amino acid analysis and mass spectrometry. Patients (n = 117) from India, Korea, Venezuela and Iran, reporting perennial respiratory indoor allergies with IgE-sensitization to cockroach (Periplaneta americana and/or Blattella germanica) were included. The sensitization profile was monitored by experimental ImmunoCAP testing. Results: ImmunoCAP testing confirmed IgE-sensitization to Periplaneta and/or Blattella extract in 98/117 patients (r = 0.95). Five out of 117 patients were sensitized to only one of the two cockroach species. The prevalence of sensitization to individual allergens varied from 4% (Per a 2) to 50% (Per a 9), with the highest IgE-values to Per a 9. Patients from four countries displayed different sensitization profiles and none of the Periplaneta components appeared as a dominant and major allergen. Periplaneta-derived lipocalin and myosin light chain were characterized as new minor allergens, designated as Per a 4 and Per a 8. Periplaneta extract showed higher diagnostic sensitivity than all individual components combined, suggesting the existence of allergens yet to be discovered. Conclusion: Utilization of a panel of purified Periplaneta allergens revealed highly heterogeneous sensitization patterns and allowed the classification of lipocalin and myosin light chain from Periplaneta as novel minor allergens.